GENETIC VARIATION OF HUMPBACK GROUPER (Cromileptes altivelis) ON F1 AND F3 GENERATIONS - Sari Budi Moria Sembiring; Tridjoko Tridjoko; Haryanti Haryanti (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
Hatchery and culture technology of Humpback grouper has been developed. However, sometimes it is still found constraint in sedd production and caused instability of production due to failure by many factors. Breeding program become necessary to provide seed with high quality and good genetic variation. Quantitative characteristic selection is one of breeding program to improve productivity in grouper aquaculture. The aim of this research was to produce good phenotyphic and genotypic quality of Humpback grouper candidate broodstock. Selection of Humpback grouper F1 and F3 was done based on quantitative characteristic (body length and weight) and genotyphic characteristic by using ramdom amplified polymorphism DNA (RAPD) method. The results of conventional selection were found candidate broodstock of Humpback grouper F1 and F3 with body weight range from 170-210 g and 160-170 g consecutively. Heterozygosity values of Humpback grouper analized by RAPD of F1 and F3 were 0.7940 and 0.7749 consecutively and it was not significantly different. This value emphasis that population of this F3 Humpback grouper was still good to grow for broodstock. Keywords: genetic variation, humpback grouper, F1, F3.